Tax Goes To Market (Community Service Activity By "Laskar BANG Kojib") - Hengky Veru Purbolakseto (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
In an effort to encourage the voluntary fulfillment of tax obligations (voluntary tax compliance) and encourage the contribution of state revenue, an independent group is needed that can provide socialization and assistance to the community in fulfilling their obligations in the field of taxation. This independent group can be represented by Real Work Lecture students with the theme "Laskar BANG Kojib" (Laskar Bersinerginya Anak Negeri Gelorakan Konstribusi Wajib). The results of the screening of potential taxpayers in the Sungailiat sub-district area by Laskar BANG Kojib until the activity was completed were 592 WP consisting of 411 employees and 181 entrepreneurs, this number is 78% of the targeted 760 new NPWP.